The Identification of Ex Nihilo with Emanation in Gregory of Nyssa - Wolfson, Harry A. (Harvard theological review, 1970)
From the fourth century on, whenever Church Fathers stressingly point to the distinction between the Word and the world as a distinction between that which was generated from God and that which was created from nothing, they aim, we may assume, not only at the Arian contention that the Word was created from nothing but also at the Plotinian view that the world was generated, that is, emanated, from God. It is this double target that is aimed at by Athanasius in a passage where he contrasts the Word with the world. The Word, he says, is a generated being (?????µa) or a son and, as such, he is the proper offspring (?????µa) of the essence, not subject to will, and hence is one who must always be.